Doprinos definiranju cjeline i dijelova integralnih transportnih sustava - Ivo Marković (Promet - Traffic&Transportation, 1970)
New transport technologies can be grouped with reference to their engineering and technological characteristics into different systems, sub-systems and segments. However, in this process of grouping i.e. defining the modalities and terms it is indispensable to reach a unique standardized definition in domestic and international relations in order to avoid diverse terms for one and the same sub-system. Thus in practice we meet different terms for new transport technologies: integrated transport, combined transport, means of modern transport technologies, integrated transport systems, new transport technologies, etc. Up to this point in time only multi-modal transport (MT) has been defined from engineering/technological, management and legal aspects by acceptance of the Convention on Multi-modal transport on the part of the United Nations (UN), UNCTAD, in the year 1980. As other modern transport systems have not been defined so far or standardized on the model of the MT the author in this paper advocates a uniform and unique name of Integrated Transport Systems for the following three basic systems: Integrated Transport, Multi-modal Transport, Combined Transport, while each and every of them keeps its sub-systems and segments as presented in Figure l . The definition has been dealt with through synthesis and analysis considering engineering and technological characteristics, their compatibility, incompatibility and other relevant factors.